2003
DOI: 10.3758/bf03196102
|View full text |Cite
|
Sign up to set email alerts
|

Change in perceptual form attenuates the use of the fluency heuristic in recognition

Abstract: Four experiments (total N = 295) were conducted to determine whether within-modality changes in perceptual form between the study and the test phases of an experiment would moderate the role of the fluency heuristic in recognition memory. Experiment 1 showed that a change from pictures to words reduced the role of fluency in recognition memory. In Experiment 2, the same result was found using counterfeit study lists that supposedly consisted of pictures or words. Experiments 3 and 4 showed that changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 66 publications
10
67
1
Order By: Relevance
“…The order of study and test items was randomIf the Jacoby-Whitehouse illusion is caused by familiarity-based attributions occurring at retrieval, then it should be eliminated by the use of a recollection-based distinctiveness heuristic. Westerman, Miller, and Lloyd (2003) reported results that were consistent with this hypothesis. They found that the Jacoby-Whitehouse illusion was eliminated in a condition in which subjects studied pictures in comparison with visual words (always using visual words at test).…”
Section: Methodssupporting
confidence: 82%
See 2 more Smart Citations
“…The order of study and test items was randomIf the Jacoby-Whitehouse illusion is caused by familiarity-based attributions occurring at retrieval, then it should be eliminated by the use of a recollection-based distinctiveness heuristic. Westerman, Miller, and Lloyd (2003) reported results that were consistent with this hypothesis. They found that the Jacoby-Whitehouse illusion was eliminated in a condition in which subjects studied pictures in comparison with visual words (always using visual words at test).…”
Section: Methodssupporting
confidence: 82%
“…Further, each condition contained a study format that was different from the test format (auditory words or pictures). Westerman, Lloyd, and Miller (2002) reported that a study-to-test modality shift (i.e., auditory study-visual test) minimized the Jacoby-Whitehouse illusion, much like the picture condition of Westerman et al (2003). If study-to-test mismatches were responsible for prior effects and recollective distinctiveness played no role, then these results suggest that using auditory presentation at study should have similar effects as would using picture presentation at study in our task.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…As regards the mere exposure effect and recognition literature, a growing body of research has provided evidence suggesting that participants do not systematically perceive fluency due to pre-exposure as a useful cue for their recognition or liking decisions (e.g., Verfaellie & Cermak, 1999;Westerman, Miller, & Lloyd, 2003;Westerman, Lloyd, & Miller, 2002;Whittlesea & Williams, 1998, 2001aWillems, Bastin, & Van der Linden, 2007;Willems & Van der Linden, 2006). In fact, it seems that the use of fluency as a cue is subject to metacognitive control and that the relationship between the judgment responses and fluency is indirect, mediated by attributional processes (Bornstein & D'Agostino, 1992, 1994Jacoby & Dallas, 1981;Kelley & Rhodes, 2002) and moderated by participants' assessment of its relevance (Westerman, Lloyd, & Miller, 2002;Westerman, Miller, & Lloyd, 2003;Willems & Van der Linden, 2006). These findings may shed some light on the role of fluency in the object decision task.…”
Section: Non-analytic and Analytic Strategiesmentioning
confidence: 99%
“…In the literature, it has been argued that the mature implementation of a strategic heuristic requires inferential processes (Westerman, Miller, & Lloyd, 2003) that could be subject to effortful regulation (e.g., Miller & Lloyd, 2011). Therefore, once children attain a sufficient level of cognitive maturity, it is possible that they begin to apply effortful control to their learning and use of heuristics, thus becoming less sensitive to implicit environmental contingencies.…”
Section: Introductionmentioning
confidence: 99%